Blood urea nitrogen to serum albumin ratio is associated with all-cause mortality in patients with AKI: a cohort study - Shi, Yue; Duan, Hangyu; Liu, Jing; Shi, Xiujie; Zhang, Yifan; Zhang, Qi; Zhao, Mingming; Zhang, Yu (Frontiers in Nutrition, 2024)
Background: This study aimed to investigate the relationship between blood urea nitrogen to serum albumin ratio (BAR) and all-cause mortality in patients with acute kidney injury (AKI), and to evaluate the effect of BAR on the prognosis of AKI.Methods: Adult patients with AKI admitted to ICU in the Medical Information Mart for Intensive Care IV (MIMIC-IV) were selected in a retrospective cohort study. BAR (mg/g) was calculated by initial blood urea nitrogen (mg/dl)/serum albumin (g/dl).According to the BAR, these patients were divided into quartiles (Q1-Q4). Kaplan-Meier analysis was used to compare the mortality of the above 4 groups. MultivariateCox regression analysis was used to evaluate the association between BAR and 28-day mortality and 365-day mortality. The receiver operating characteristic (ROC) curve was plotted and the area under the curve (AUC) was calculated, and the subgroup analysis was finally stratified by relevant covariates.Results: 12125 patients with AKI were included in this study. The 28-day and 365-day mortality rates were 23.89% and 39.07%, respectively. Kaplan-Meier analysis showed a significant increase in all-cause mortality in patients with high BAR (Log-rank P < 0.001). Multivariate Cox regression analysis showed that BAR was an independent risk factor for 28-day mortality (4.32BAR≤7.14: HR 1.12, 95% CI 0.97-1.30, P=0.114;